(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Amitav Ghosh’s new novel, The Hungry Tide, is rich inworldly lore. The paper is set in theSundarbans, “an immense archipelago of islands….interposed between the sea andthe plains of Bengal”. The setting suggested vivid possibilities. Floodscontinually submerge the scattered bodies of land. Whole forests life theirheads above the tides and then disappear. Fresh and salty channels cut intoeach other, creating a diverse natural habitat. The only permanent thing is thewater. Whatever is human has to pick its spots among the inconstant islands.